The perception of dancers on the congruence between music and movement in a rhythmic gymnastics routine - Loo, Fung Chiat; Loo, Fung Ying (Marsland Press, 2014)
The issue of using music synchronously or asynchronously in the field of dance has long been discussed by scholars and practitioners. In sports which involve a routine, it has been observed that some athletes use music merely as a background effect while others opt to choreograph routines in close congruence with musical details. This paper aims to investigate the perception of respondents who have a background in dancing of the congruence between movements and music in a rhythmic gymnastics routine. The study also intended to investigate the quality of the enhanced music accompaniment in the selected sports routine. A routine performed by a gymnast was recorded and new music, closely synchronized with every movement of the gymnast, was composed based on the existing choreography. Fifty-six ballerinas were presented with two videos. Both videos show the same routine, but one has the original music used by the gymnast and the other, the new music. Through a survey, the respondents were asked to choose which video presented the performance in which music and the routine are more congruent. The result shows that the routine accompanied by new music was mostly chosen by the respondents. Of the many elements, tempo and climax in the new music were considered to be the most significant in the congruence between music and routine.